VILLAGE PROPERTY HOUSE CONSTRUCTION AGREEMENT ACCORDING TO SHARIA ECONOMIC LAW: A STUDY IN DARUSSALAM SUB-DISTRICT, ACEH BESAR - Dahra, Maulia; Razak, Abd (JURISTA: Jurnal Hukum dan Keadilan, 2024)
An employment agreement in the form of an ijarah ‘ala al- ’amal contract as an agreement in Islamic economic law is a form of agreement that employs someone who has soft skills or hard skills to do a job. This type of research is a qualitative descriptive approach through case studies. The results of the study found that the house construction agreement was carried out orally so that there was a discrepancy between what was promised and what was done. The existence of default is because the worker does not carry out the obligations of what is an agreement in the agreement between the two parties. The problem experienced between the contractor and the worker, where the worker broke the promise to the contractor because he did not complete the deadline that had been determined, but when it was due suddenly the worker was not ready to work on the construction of the house. So this is detrimental to his superior, namely the contractor. Meanwhile, in the ijarah ala al amal contract, there must be clarity, certainty, and suitability, while this worker did not make any discrepancies with the contractor.